Knowledge, Perceptions, and Perspectives of Medical Students Regarding the Use of Antibiotics and Antibiotic Resistance: A Qualitative Research in Galicia, Spain - Juan M. Vázquez-Lago; Rodrigo A. Montes-Villalba; Olalla Vázquez-Cancela; María Otero-Santiago; Ana López-Durán; Adolfo Figueiras (MDPI AG, 2023)
Antibiotic resistance is a significant public health concern, with numerous studies linking antibiotic consumption to the development of resistance. As medical students will play a pivotal role in prescribing antibiotics, this research aimed to identify their perceptions of current use and factors that could influence future inappropriate use of antibiotics. The study employed a qualitative research approach using Focus Group discussions (FGs) consisting of students from the final theoretical course of the Medicine degree. The FGs were conducted based on a pre-script developed from factors contributing to antibiotic misuse identified in previous studies. All sessions were recorded and transcribed for analysis by two independent researchers, with all participants signing informed consent. Seven focus groups were conducted, with a total of 35 participants. The study identified factors that could influence the future prescription of antibiotics, including the low applicability of knowledge, insecurity, clinical inertia, difficulties in the doctor-patient relationship, unawareness of available updates on the topic, and inability to assess their validity. The students did not perceive antibiotic resistance as a current problem. However, the study found several modifiable factors in medical students that could explain the misuse of antibiotics, and developing specific strategies could help improve their use.